D-Stereoisomer preference of the OmpA-like domain of Pal in peptidoglycan of Acinetobacter baumannii. (April 2017) - Yeo, Kwon Joo; Lee, Woo Cheol; Lee, Saeyoung; Hwang, Eunha; Park, Jeong Soon; Choi, In-Geol; Kim, Seung Il; Lee, Je Chul; Jeon, Young Ho; Cheong, Chaejoon; Kim, Hye-Yeon
Graphical abstract: Highlights: Structures of peptidoglycan-associated lipoprotein of Acinetobacter baumannii. . Peptidoglycan-associated lipoprotein in complex withd - orl -diaminopimelate. d -Stereoisomer preference of peptidoglycan-associated lipoprotein. Abstract: OmpA-like domain proteins bind to peptidoglycan by interacting with thed -amino acid moiety of meso -diaminopimelate in peptidoglycan, but it is still not clear how this domain recognizes thed -amino region of peptidoglycan. To study theird -stereoisomer preference, we solved the crystal structures of the OmpA-like domains of Acinetobacter baumannii peptidoglycan-associated lipoprotein (AbPal) in complex withd - orl -diaminopimelate. Our results reveal that these domains can bind both enantiomers of diaminopimelate with a greater affinity ford -diaminopimelate. The crystal structures of wild-type AbPal in complex with meso -diaminopimelate and mutant AbPal in complete with thel l -diaminopimelate ligand suggests that the Tyr85 residue of AbPal is an important determinant for thisd -amino acid moiety preference. Our findings provide a basis for the development of antibacterial agents that inhibit interactions between PGN and OmpA-like domains and disrupt the stability of cell walls of gram-negative bacteria.